Collaboration in Preparing Early Childhood Readiness to Enter Elementary School through Habituation Programs - Sri Rahayu; Ardhana Januar Mahardhani; Betty Yulia Wulansari (Institut Agama Islam Negeri Palopo, 2025)
This research examines the collaboration across different levels among kindergartens, elementary schools, and parents in facilitating children's readiness for the transition to elementary school via a shared lunchbox acclimatization initiative at TK-IT Ar Rohmah Magetan. The subject is crucial since early transitions greatly influence children’s autonomy, social abilities, and preparedness for learning. A qualitative case study methodology was utilized to gather data via direct observation, comprehensive interviews with educators, open-ended surveys from 28 parents, and analysis of documents. The research suggests that organized teamwork improves children's preparedness for school. Findings indicate that collaborative initiatives—like synchronized lunch menus, elementary teachers visiting kindergartens, and combined parenting workshops—enhance communication among stakeholders and foster better habits in children's table manners, discipline, and health. A significant discovery is the proactive involvement of elementary teachers as transition collaborators instead of merely receiving kindergarten graduates passively. This change enables more seamless and contextually fitting transitions. The research provides actionable insights for Islamic educational organizations to implement a cooperative habituation framework that incorporates character development from a young age.